Microscopic features of raw materials of Laurus nobilis L. - S. G. Musienko; V. S. Kislichenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The urgent task of contemporary pharmacy is the continuation of studies of popular medicinal plants’ raw materials, for example, laurel, for further adjustment of its application. To establish diagnostic microscopic features the anatomic structure of laurel shoots and leaves has been studied using well-known micro technical techniques.